Employers’ perception of the law syllabus content of practicum course in Universiti Utara Malaysia - Hassan, Mumtaj (IAMURE Multidisciplinary Research, 2012)
Practicum courses are guided work experiences that consist of a project undertaken for or in collaboration with an organization.This study is an exploratory research carried out to evaluate objectively the present structure of the practicum course for LL.B students at University Utara Malaysia.The study examined the employer’s perception of the syllabus contents of practicum I and II.The specific aspects of the syllabus contents examined were the employer’s perception towards the objectives of the course, learning outcome and the duration of the course. The items also include the content as to the administrative, report writing, judgment, supervisory aspect and the method of assessment.The study was carried out amongst the experience legal practitioners who were the assessors of the students undergoing practical training at their placements.Data was collected using a survey questionnaire.A total of 51 questionnaires were sent out.The total responses received were 43 (83.31%). The findings indicate that the majority of respondents generally (more than 80%) agree that the syllabus contents were good and suitable for practicum I and II courses.Nevertheless, they are of the opinion that there is a need to extend the existing duration of the practicum training for the students.